1999
DOI: 10.1002/(sici)1099-1573(199905)13:3<254::aid-ptr430>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of verbascoside on the isolated rat heart: increases in level of prostacyclin

Abstract: The mechanism of the positive cardioactive effects induced by verbascoside in the Lagendorff rat heart has been investigated. Isolated rat hearts treated with α‐ or β‐ adrenergic agents did not show significant reduction of the positive chronotropism, inotropism and increased coronary perfusion rate mediated by verbascoside. A significant increase in prostacyclin levels (142%) observed following the administration of verbascoside suggests that prostacyclin stimulates formation of cAMP which induces the cardioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This suggests that these flavonoids are not the only responsibles for the antispasmodic effect of Aloysia citriodora. Regarding the presence of verbascoside in this plant (Carnat et al, 1999) there are several reports about its effects as antitumoral (Kunvari et al, 1999), antioxidative (Liu et al, 2003) and cardiac inotropic and chronotropic (Pennacchio et al, 1999), but none on smooth muscle. Further studies will be necessary to identify other components responsible for the antispasmodic effect of "cedrón".…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that these flavonoids are not the only responsibles for the antispasmodic effect of Aloysia citriodora. Regarding the presence of verbascoside in this plant (Carnat et al, 1999) there are several reports about its effects as antitumoral (Kunvari et al, 1999), antioxidative (Liu et al, 2003) and cardiac inotropic and chronotropic (Pennacchio et al, 1999), but none on smooth muscle. Further studies will be necessary to identify other components responsible for the antispasmodic effect of "cedrón".…”
Section: Discussionmentioning
confidence: 94%
“…Verbascoside significantly increased heart rate, contractile force and coronary perfusion rate in isolated Langendorff rat hearts. Those changes occurred in response to increases to intracellular cyclic adenosine monophosphate levels (Pennacchio et al, 1996b), which appeared to be induced by increased levels of prostacyclin (Pennacchio et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Verbascoside is the index component of Rehmanniae Radix Praeparata. It has some effects such as being neuroprotective [31], antipneumonia [32], antifatigue [33], being cardiotonic [34], etc. Research showed that verbascoside could have competitive binding estrogen receptors in Hela with estradiol, antagonizing the upregulation of ERE luciferase activity by estradiol.…”
Section: Biopathway Affected By Verbascosidementioning
confidence: 99%